2021
DOI: 10.1002/bab.2126
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement and mechanisms of MC3T3‐E1 osteoblast‐like cell adhesion to albumin through calcium exposure

Abstract: Serum albumin is the most prominent protein in blood, and it aids in bone fracture healing, though the manner through which enhanced healing occurs is not well understood. This study investigates the influence of calcium on the bioactivity of albumin due to the prevalence of calcium at bone injury sites. Bovine serum albumin (BSA) was exposed to varying concentrations of calcium, adsorbed to tissue culture polystyrene, and the subsequent BSA-coated surfaces were evaluated with calcium titration, and cell adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 43 publications
3
31
0
Order By: Relevance
“…35 Recently, our group investigated the impact of calcium on the bioactivity of albumin, based on the hypothesis that calcium interactions may induce a bioactive conformational state of albumin. 38 In support of this hypothesis, we found an increase in osteoblast-like cell (MC3T3-E1) adhesion to calcium modified bovine serum albumin (BSA) adsorbed on tissue culture polystyrene (TCPS) surfaces, that correlated with the calcium exposure level. These cell culture results were supported by molecular dynamics simulations, which demonstrate calcium induced unfolding of BSA.…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…35 Recently, our group investigated the impact of calcium on the bioactivity of albumin, based on the hypothesis that calcium interactions may induce a bioactive conformational state of albumin. 38 In support of this hypothesis, we found an increase in osteoblast-like cell (MC3T3-E1) adhesion to calcium modified bovine serum albumin (BSA) adsorbed on tissue culture polystyrene (TCPS) surfaces, that correlated with the calcium exposure level. These cell culture results were supported by molecular dynamics simulations, which demonstrate calcium induced unfolding of BSA.…”
Section: Introductionmentioning
confidence: 63%
“…It has been suggested that BSA provides benefits to healing when provided to injury sites, [25][26][27][28][29][30][31][32][33][34] so this work is focused on the delivery of calcium modified, bioactive BSA. 38 Polyampholyte hydrogels were selected as the delivery approach due to their demonstrated multi-functional nonfouling and protein delivery capacity, 22 which may prove beneficial for future in vivo applications. Because TMA:CAA hydrogel scaffolds have previously been extensively characterized, [20][21][22] this work is instead focused on the MC3T3-E1 cellular response to calcium modified BSA delivered from this platform.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations